1995
DOI: 10.1007/bf02347863
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of soil respiration using closed chamber method: An IRGA technique

Abstract: A dosed chamber method (CC-method) using an infra-red gas analyzer (IRGA) for measuring soil respiration Was examined. Two major factors which potentially cause errors: (i) volume of air sampled from the chamber; and (ii) measuring period of time, were examined in laboratory experiments. Field measurements were also conducted with both the CC-method and the open-flow IRGA method (OF-method) throughout a year. The results of laboratory experiments showed that (i) sampling volume of air should be less than 0.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 13 publications
0
37
1
1
Order By: Relevance
“…This result was expected, as there is good reason to assume that the fluxes reported by von Arnold et al (2005a) partly underestimated the true community flux, since the flux was determined by static chambers over a rather long measuring time (15-30 min). According to Bekku et al (1995), sampling intervals longer than 20-25 min underestimate the CO 2 flux. Similar results have been reported by Pumpanen et al (2004), who found that chamber measurements during 30 min underestimated the soil CO 2 flux by about 15%, compared with 10 min of measuring time.…”
Section: Performance Of the Calibrated Model Using Mean Parameter Valuesmentioning
confidence: 98%
“…This result was expected, as there is good reason to assume that the fluxes reported by von Arnold et al (2005a) partly underestimated the true community flux, since the flux was determined by static chambers over a rather long measuring time (15-30 min). According to Bekku et al (1995), sampling intervals longer than 20-25 min underestimate the CO 2 flux. Similar results have been reported by Pumpanen et al (2004), who found that chamber measurements during 30 min underestimated the soil CO 2 flux by about 15%, compared with 10 min of measuring time.…”
Section: Performance Of the Calibrated Model Using Mean Parameter Valuesmentioning
confidence: 98%
“…This indicates that CO 2 emission could be underestimated if longer sampling intervals are used, which is often the case when gas samples are collected for gas chromatography analysis. Bekku et al (1995) suggest avoiding sampling intervals longer than 20-25 minutes, while Pumpanen et al (2004) report that nonsteady state non-throughflow chambers underestimate the soil CO 2 flux by about 15% when using 30-minute sampling intervals compared with 10-minute intervals. In our very limited investigation, the underestimation was 56% (Figure 7), but this is a dynamic number dependent on emission rate.…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…All gas sampling was conducted during 13:00 and 15:00 by measuring 20 places at once. A previous experiment showed that GHG fluxes from soil could be sufficiently detected within 20 min (Bekku et al 1995). Thus, gas samples were taken 1, 7, 15, and 21 min after the closure of the chamber.…”
Section: Gas and Soil Sampling And Measurement Of Environmental Factorsmentioning
confidence: 99%
“…In this method, GHG concentration is periodically sampled in a closed chamber to calculate the efflux from the rate of increase or decrease of the gas concentration. The closed-chamber method is used widely due to its convenience, even though a dynamic chamber has a smaller impact on the internal conditions due to its aeration (Bekku et al 1995).…”
Section: Introductionmentioning
confidence: 99%